2009
DOI: 10.2478/s11756-009-0043-5
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an optimized Aspergillus sulphureus β-mannanase gene in Pichia pastoris

Abstract: β-Mannanase (EC 3.2.1.78) is a key enzyme to hydrolyze the β-mannosidic linkages in mannan and heteromannan. The expression of a wild type β-mannanase (manWT) of Aspergillus sulphureus in Pichia pastoris is not high enough for its application in feed supplement. To earn a high expression level, the manWT gene was firstly optimized to manM according to the code bias of P. pastoris, which was then inserted into pPICzαA and transformed into P. pastoris strain X-33. In the induction by methanol, β-mannanase was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…During the past few years, numerous β-mannanase’s have been purified and characterized from various organisms including bacteria, yeasts, fungi and plants ( Cai et al, 2011 ). Our laboratory has expended a considerable amount of effort aimed at the development of β-mannanase’s for the food, pulp, and paper and oil drilling industries ( Chen et al, 2007 ; 2008 ; 2009 ; Li et al, 2010 ; Qiao et al, 2010 ; Cai et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, numerous β-mannanase’s have been purified and characterized from various organisms including bacteria, yeasts, fungi and plants ( Cai et al, 2011 ). Our laboratory has expended a considerable amount of effort aimed at the development of β-mannanase’s for the food, pulp, and paper and oil drilling industries ( Chen et al, 2007 ; 2008 ; 2009 ; Li et al, 2010 ; Qiao et al, 2010 ; Cai et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…After the effect of different concentrations of methanol in the BMMY medium on the recombinant A. niger β-mannanase production by the GSKZαM2 strain was examined, we found that 1.5% (v/v) methanol in the BMMY medium was most suitable for induction for the recombinant A. niger β-mannanase production and the optimal induction time was 7 days. Under optimal conditions, 222.8 U/mL of β-mannanase activity was produced, which was higher than that of β-mannanase expressed in P. pastoris by codon optimization and double vector system (Chen et al, 2009;Tang et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…The bias of codon usage has been demonstrated to be related to gene expression level (Sharp & Li 1986). In our previous studies, expression level of enzymes, such as β-mananase and β-xylanase, could be significantly increased by codon optimization (Cao et al 2007;Chen et al 2009). In this study, the optimized gene glu-opt coded for B. subtilis MA139 β-1,3-1,4-glucanase was overexpressed with a yield of 15,000 U/mL in a 10-L fermentor.…”
Section: Characterization Of the Recombinant β-13-14-glucanasementioning
confidence: 99%